Bridging the gap from medical to psychological safety assessment: consensus study in a digital mental health context - Taher, R; Bhanushali, P; Allan, S; Alvarez-Jimenez, M; Bolton, H; Dennison, L; Wallace, BE; Hadjistavropoulos, HD; Hall, CL; Hardy, A; Henry, AL; Lane, S; et al. (Cambridge University Press, 2024)
Background: Digital Mental Health Interventions (DMHIs) that meet the definition of a medical device are regulated by the Medicines and Healthcare products Regulatory Agency (MHRA) in the UK. The MHRA uses procedures that were originally developed for pharmaceuticals to assess the safety of DMHIs. There is recognition that this may not be ideal, as is evident by an ongoing consultation for reform led by the MHRA and the National Institute for Health and Care Excellence.